PERANCANGAN SISTEM INFORMASI PENGENDALIAN PERSEDIAAN BAHAN BAKU DENGAN PENDEKATAN METODE EOQ DI PT XYZ - Rafi Rafi; Yustina Ngatilah (Tekmapro : Journal of Industrial Engineering and Management, 2022)
Raw materials are one of the important elements in the production process at PT XYZ. Therefore, controlling the inventory of raw materials needs special attention to prevent fluctuating and various inventory problems. PT. XYZ has problems in the process of recording and planning raw materials which are still manual in the notebook, as well as difficulties in determining the exact quantity and timing of determining which have been estimated so far. In this case, of course, it takes a lot of time and is inaccurate in calculating and recording it. This study has the aim of designing a raw material inventory information system using the EOQ approach. The system is built using Visual Basic language and Microsoft Access database. Based on the results obtained, the inventory information system is designed to store data and transactions related to raw materials. With this supply program, it can help PT. XYZ overcomes existing problems by storing raw material transactions, determining the correct amount and time of reorder with the existence of EOQ and ROP.